Evaluating the environmental effects of Japan's tourism: insights into pandemic-induced changes and driving forces - Yuzhuo Huang; Yosuke Shigetomi; Ken’ichi Matsumoto (Environmental Research Communications)
The intersection of the COVID-19 pandemic and tourism has significantly influenced emissions from supply chains, highlighting a complex dynamic between tourism and climate change. Although the pandemic represents a unique event within a specific timeframe, analyzing its impact on tourism provides valuable insights into the characteristics of tourism carbon footprints (TCF) in the context of sudden public health crises. Accordingly, we used the latest data available from the global multi-regional input–output table of EXIOBASE3 and Japan’s tourist consumption statistics to estimate the TCF from all tourist sources in Japan based on the global economic system, and we visualized the carbon flow caused by population mobility. The decomposition of the environmental impact of the pandemic response further identified the driving forces of TCF changes. The main findings suggested that substantial differences exist in the emission levels and sectoral distributions of TCF between inbound and domestic tourism in Japan. Domestic TCF accounted for the majority of the overall TCF, and it also showed a stronger ability to withstand the pandemic impact, accounting for over 90% of Japan’s TCF during the pandemic. The pandemic greatly reduced the TCF and further exacerbated the driving differences. Prior to the pandemic, Japan’s TCF had diverse driving forces; however, pandemic-induced restrictions magnified the volume effect, especially in the inbound TCF, whereas other effects remained substantial for the domestic TCF.